The Force Scheme in Javanese Emotion Metaphors - Rahardian, Ema; Nirmala, Deli (Master Program in Linguistics, Diponegoro University, 2018)
People with their creativity can use language for different purposes with different attitudes. They use metaphors in daily communication. In this paper, the writer tried to analyze them from force schemas to show the cognitive patterns of the users’ mind. . This paper aims at discussing the use of force schema in Javanese EMOTION metaphor. To collect the data, the writer used non-participant observation supported by note-taking technique. To choose the samples, the writers used purposive sampling technique. This means that the writers only took the metaphorical expressions containing a concept of emotion especially force schema conceptualization. To analyze the data, the writers used referential identity method. The writers used the method to uncover the meaning and the attitude of the speakers in using the expressions. The writer found that force schema used in Javanese EMOTION metaphors are compulsion, enablement, diversion, and restraint-removing force schemas. The writer also found that Javanese people have active and inactive responses when they get emotion. This finding may add more studies on metaphors.